2015
DOI: 10.4196/kjpp.2015.19.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Predominant D1Receptors Involvement in the Over-expression of CART Peptides after Repeated Cocaine Administration

Abstract: The aim of this study was to investigate the involvement of dopaminergic receptors (DR) in behavioral sensitization, as measured by locomotor activity, and the over-expression of cocaine- and amphetamine-regulated transcript (CART) peptides after repeated administration of cocaine in mice. Repeated administrations of cocaine induced behavioral sensitization and CART over-expression in mice. The levels of striatal CART mRNA were significantly increased on the 3rd day. CART peptides were over-expressed on the 5t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Previous studies indicated that injection of GABA B R agonist baclofen or GABA B R positive allosteric modulators can attenuate self-administration and drug craving in ethanol-dependent rats and human alcoholics ( Addolorato et al ., 2006 ; Knapp et al ., 2007 ). Recently, we have shown the modulatory effect of intra-accumbally injected CART peptide on methamphetamine-induced depression of GABA B R-GIRK signaling and concomitant internalization and reduction of membrane GABA B R and GIRK receptors in the VTA and mPFC neurons ( Hu et al ., 2015 ), which suggests the regulatory targets of CART peptide are similar to those of the positive allosteric modulator GABA B R on GABA B1 R and GABA B2 R in the context of rescue from drug-depressed GABA B R-GIRK signaling ( Fig. 2 ).…”
Section: Relations Between Cart Containing Neural Circuits and Depresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that injection of GABA B R agonist baclofen or GABA B R positive allosteric modulators can attenuate self-administration and drug craving in ethanol-dependent rats and human alcoholics ( Addolorato et al ., 2006 ; Knapp et al ., 2007 ). Recently, we have shown the modulatory effect of intra-accumbally injected CART peptide on methamphetamine-induced depression of GABA B R-GIRK signaling and concomitant internalization and reduction of membrane GABA B R and GIRK receptors in the VTA and mPFC neurons ( Hu et al ., 2015 ), which suggests the regulatory targets of CART peptide are similar to those of the positive allosteric modulator GABA B R on GABA B1 R and GABA B2 R in the context of rescue from drug-depressed GABA B R-GIRK signaling ( Fig. 2 ).…”
Section: Relations Between Cart Containing Neural Circuits and Depresmentioning
confidence: 99%
“…Recently, CART peptide has been suggested to positively and allosterically modulate γ-aminobutyric acid B receptors (GABA B R), based on the observation that it inhibited drug-depressed GABA B R-G-protein-coupled inwardly rectifying K + -channel (GIRK) signaling. Thus, it has been suggested CART peptide modulates psychostimulant-induced hyperlo-comotion through DR-related calcium signaling and GABA-R-associated pathways ( Moffett et al ., 2011 ; Upadhya et al ., 2012 ; Cai et al ., 2014 ; Hu et al ., 2015 ; Fu et al ., 2016 ; Xiong et al ., 2018 ). However, our understanding of CART pathways in neuronal circuits is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic axons terminate on accumbal CART neurons (Smith et al, 1999;Upadhya et al, 2012). Dopamine D1, D2, and D3 receptors are expressed on these neurons (Beaudry et al, 2004;Hubert and Kuhar, 2006) and striatal CART expression is regulated by dopamine receptors (Beaudry et al, 2004;Hu et al, 2015;Hunter et al, 2006). Also, Leshan et al (2010) showed that some VTA neurons project to and regulate CART neurons in the AMG.…”
Section: Introductionmentioning
confidence: 99%
“…Leshan et al (2010) showed that a subclass of VTA dopaminergic neurons project to and regulate CART neurons in the CeA. Furthermore, there are studies suggesting either an up-regulatory effect of D1, D2, and D3 receptors or a down-regulatory effect of D3 receptor on CART expression (Beaudry et al, 2004;Hu et al, 2015;Hunter et al, 2006).…”
mentioning
confidence: 99%
“…In turn, CART peptides can regulate locomotor activity via dopamine receptor and cAMP/PKA/pCREB signaling pathway activities. Our previous report showed that cocaine- and caffeine-induced sensitization was expressed on the 5 th day of administration and that CREB phosphorylation and CART peptide expression peaked on the 5 th day [ 28 , 29 ]. In the present study, we examined the effects of CART peptides on locomotor activity and CREB phosphorylation on the 5 th day of caffeine administration.…”
Section: Introductionmentioning
confidence: 99%